Health Insurances and the Health-Related Work Capacity of Retirement-Aged Workers: A Comparative Investigation. Issue 3 (29th March 2022) - Li, Jiannan; Yuan, Bocong
Abstract : Systematic inequity across different health insurances can bring risk to retirement-aged workers and lead to their contrasting health outcomes. Policymakers need more fine-grained design of health insurances to better protect retirement-aged workers. Abstract : Objective: This study is to investigate the health-related work capacity of retirement-aged workers under the beneficiary status of different health insurance schemes in China. Method: Using the data from CHARLS program, we investigate the health-related work capacity of retirement-aged workers in China (more than 60/55 years-old for men/women respectively). Multivariate regressions and robustness checks (Heckman two-stage procedures, chronological design, etc) are conducted. Results: (1) Late-life career participation could reduce the risk of declining work capacity due to health problems; (2) different social health insurances affect health-related work capacity among retirement-aged workers differently; (3) social health insurances influence the role of late-life career participation in reducing the risk of health-related work capacity, with different schemes displaying different effects (mitigate or strengthen). Conclusions: Systematic inequity in benefit across health insurances may result in contrasting health outcomes of retirement-aged workers.